2016
DOI: 10.1111/imm.12614
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A or E and a catechin synergize as vaccine adjuvant to enhance immune responses in mice by induction of early interleukin‐15 but not interleukin‐1β responses

Abstract: Vitamins A and E and select flavonoids in the family of catechins are well-defined small molecules that, if proven to possess immunomodulatory properties, hold promise as vaccine adjuvants and various therapies. In an effort to determine the in vivo immunomodulatory properties of these molecules, we found that although mucosal and systemic vaccinations with a recombinant HIV-1 BaL gp120 with either a catechin, epigallo catechin gallate (EGCG) or pro-vitamin A (retinyl palmitate) alone in a vegetable-oil-in-wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(55 reference statements)
1
14
0
1
Order By: Relevance
“…Similarly, in the present study, supplementation of GS in SO has been found to increase antibody responses 2 weeks after the booster immunization. VE has been reported to exert immunostimulatory activities as an adjuvant to various vaccines and formulated in AS03 [15][16][17][18]. The present study found similar results that addition of VE in SO increased IgG1 numerically and IgG2a significantly.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, in the present study, supplementation of GS in SO has been found to increase antibody responses 2 weeks after the booster immunization. VE has been reported to exert immunostimulatory activities as an adjuvant to various vaccines and formulated in AS03 [15][16][17][18]. The present study found similar results that addition of VE in SO increased IgG1 numerically and IgG2a significantly.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous study demonstrated that a vegetable oil containing both vitamin E and ginseng saponins (SO-VE-GS) had adjuvant effect and significantly improved the immune response induced with an FMD vaccine in mice [ 32 ]. VE included in vaccines to improve the immunostimulation has been reported in other studies [ 33 , 34 ]. Morel et al found that VE was required for an adjuvant AS03 to achieve the enhanced antibody response [ 33 ].…”
Section: Introductionmentioning
confidence: 79%
“…Unlike arginine, citrulline is known to have antioxidant activity (1). It was reported that some compounds with antioxidant activity have immunomodulatory effects although the modes of action remain unclear (7,23,27,29). When modified M2e and amyloid β peptides were used as antigens, citrulline showed much higher adjuvant activity than that of the other vaccine antigens used in this study.…”
Section: Difference In the Adjuvant Activity Mechanism Between Citrulmentioning
confidence: 74%